Adaptasi Strategi Pemasaran PT. Djarum (Grup Djarum) Melalui Cultural Shift - Dwiharjo, Untung; Ayuningtyas, Fitria; Prasetyo, Iwan Joko; Panuju, Redi (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Now the world is changing rapidly, especially after Covid 19, the world is experiencing The Great Reset (large scale changes) resulting in disruption. As a result of this, many institutions, institutions and companies have closed down because they are not ready to face these changing times. Because of the importance of this problem, in this paper we try to highlight a holding company that has successfully carried out the process of changing this era, namely the Djarum Group. In this case the problem raised is what factors play a role in the successful adaptation of PT's marketing strategy. Djarum (Djarum Group) through Cultural Shift? This paper uses the literature study method using the Djarum Group case study with a descriptive qualitative paradigm approach.  From the description it was found that the factors that played a role in the successful adaptation of PT's marketing strategy. Djarum (Djarum Group) through Cultural Shift is a strong and visionary leadership factor of two brothers, namely the Hartono Brothers who are the heirs to the founders of PT Djarum, where they have both succeeded in realizing the vision and mission of their parents when founding PT. Djarum even goes beyond this by providing a touch of innovation and sophisticated production technology. Making the Djarum Group a global company that is world-famous and the Hartono brothers are always listed as the richest people in Indonesia.